2015
DOI: 10.3171/2015.7.peds15336
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal surgery for myelomeningocele and the need for cerebrospinal fluid shunt placement

Abstract: OBJECT The Management of Myelomeningocele Study (MOMS) was a multicenter randomized trial comparing the safety and efficacy of prenatal and postnatal closure of myelomeningocele. The trial was stopped early because of the demonstrated efficacy of prenatal surgery, and outcomes on 158 of 183 pregnancies were reported. Here, the authors update the 1-year outcomes for the complete trial, analyze the primary and related outcomes, and evaluate whether specific prerandomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(188 citation statements)
references
References 13 publications
11
168
1
8
Order By: Relevance
“…This number at 1 month is lower than the published 84% shunt rate at 12 months reported in the MOMS trial. 1,3 The timing of intervention on hydrocephalus after MMC closure has yet to be defined and studied in the literature. A preliminary retrospective review of our institution's experience reveals that shunt rates are indeed appreciably lower at 1 month than at 12 months, though this complex and interesting problem deserves dedicated multiinstitutional study in the future.…”
mentioning
confidence: 99%
“…This number at 1 month is lower than the published 84% shunt rate at 12 months reported in the MOMS trial. 1,3 The timing of intervention on hydrocephalus after MMC closure has yet to be defined and studied in the literature. A preliminary retrospective review of our institution's experience reveals that shunt rates are indeed appreciably lower at 1 month than at 12 months, though this complex and interesting problem deserves dedicated multiinstitutional study in the future.…”
mentioning
confidence: 99%
“…Another case report of fetal MMC repair was excluded as it lacked details regarding the operation performed and subsequent outcomes [21]. Four articles were excluded as they reported follow-up outcomes of the MOMS [8,9,22,23]. We included the outcomes of a recently published study on a modified approach to fetoscopic MMC repair through a maternal laparotomy and excluded a case report by the same authors to avoid duplication of data [24,25].…”
Section: Study Selectionmentioning
confidence: 99%
“…Although controversial, in-utero closure of the open neural tube defect may offer some advantages to the child, but the risks of preterm labor (13% delivered at less than 30 weeks gestation) and maternal health remain significant concerns. [7][8][9] An ambitious randomized trial of 183 patients has demonstrated decreased need for ventriculoperitoneal (VP) shunts, 7 as well as improved mental and motor development, decreased hind brain herniation, and improved ambulation by 30 months. 9 Urological outcomes were not part of the initial assessment, but a 2015 review of the Management of Myelomeningocele Study (MOMS) demonstrated no difference in the need for clean intermittent catheterization (CIC), but patients appeared to have less bladder trabeculation and fewer open bladder necks.…”
Section: Prenatalmentioning
confidence: 99%
“…6,26,27 It has been shown that the most important factor in successful outcomes is proper family selection. [7][8][9]28 Bladder neck procedures range from endoscopic injections of the bladder neck to outpatient suburethral slings, to bladder neck reconstruction, to ligation or closure of the bladder neck. 7,29 Many pediatric urologists prefer a moderate approach, to leave the patient with a "pop-off" mechanism in the case of inability or unwillingness to catheterize.…”
Section: Elementary Schoolmentioning
confidence: 99%
See 1 more Smart Citation